Synthesis and biological evaluation of pyridinone analogues as novel potent HIV-1 NNRTIs. Issue 1 (1st January 2015) - Cao, Yuanyuan; Zhang, Yu; Wu, Shaotong; Yang, Quanzhi; Sun, Xuefeng; Zhao, Jianxiong; Pei, Fen; Guo, Ying; Tian, Chao; Zhang, Zhili; Wang, Haining; Ma, Liying; et al.
Graphical abstract